Deemed consent for organ donation in Northern Ireland - Jordan A. Parsons; Bonnie Venter (Elsevier, 2022)
Summary: Shortages of organs for transplantation have led many countries to introduce systems of deemed consent for organ donation, whereby donation is the default upon death and an individual must provide express opposition to donation to prevent it. Despite a lack of clear supporting evidence, it is often suggested that deemed consent will contribute significantly to addressing the organ shortage. Northern Ireland appears set to be one of the next countries to pursue this route, with the Organ and Tissue Donation (Deemed Consent) Bill currently making its way through the Northern Ireland Assembly. If passed, this Bill will see Northern Ireland follow in the footsteps of the rest of the UK. In this viewpoint, we provide an overview of Northern Ireland's progress towards introducing deemed consent and argue two related points. First, that public awareness of the policy (if introduced) is vital to both its defensibility and longevity, and that this must be recognised through the imposition of a ministerial duty to focus on such awareness. Second, that policymakers in Northern Ireland ought to support the policy to ensure consistency across the UK in organ procurement, thereby preventing Northern Ireland from disproportionately benefitting from the UK-wide organ allocation system.